Pulmonary hypertension in infants with bronchopulmonary dysplasia - Gi Beom Kim (Korean Pediatric Society, 2010)
An increase in the number of preterm infants and a decrease in the gestational age at birth have resulted in an increase in the number of patients with significant bronchopulmonary dysplasia (BPD) and secondary pulmonary hypertension (PH). PH contributes significantly to the high morbidity and mortality in the BPD patients. Therefore, regular monitoring for PH by using echocardiography and B-type natriuretic peptide (BNP) or N-terminal-proBNP must be conducted in the BPD patients with greater than moderate degree to prevent PH and to ensure early treatment if PH is present. In the BPD patients with significant PH, multi-modality treatment, including treatment for correcting an underlying disease, oxygen supply, use of diverse selective pulmonary vasodilators (inhaled nitric oxide, inhaled prostacyclins, sildenafil, and endothelin-receptor antagonist) and other methods, is mandatory.